Phytochemical screening, total phenolics and antimicrobian action from the brazilian cherry, black mulberry and blueberry fruits’ pulps (Research, Society and Development, 2022)
The demand for functional foods with exotic flavors is emerging among consumers. The fruits brazilian cherry, black mulberry and blueberry have demonstrated considerable potential as inhibitors of the growth of microorganisms. The phytochemicals present in different extracts were obtained from fruits (pulps), employing specific tests to detect classes of compounds besides Infrared. Tests were realized for antimicrobial activity and quantification of total phenolics. In the phytochemical tests, the presence of mainly the flavonoid group was observed, in agreement with the high values of total phenolics found. The 70% ethanol is the most indicated solvent because it presents greater extraction of polar clusters, besides providing signals of absorption of O-H bonds in all pulps studied. The blueberry showed fungistatic action for Candida tropicalis. The diffusion of the extract through the culture medium is difficult, consequently, the formation of a halo, visible as that of the control, too is difficult. Therefore, results obtained in this study are considered screening and not as definitive results.